2023
DOI: 10.3233/bmr-220079
|View full text |Cite
|
Sign up to set email alerts
|

Pain, deep neck flexors performance, disability, and head posture in individuals with temporomandibular disorder with and without otological complaints

Abstract: BACKGROUND: Otological complaints (OC) are highly prevalent in subjects with temporomandibular disorders (TMD) and so is the risk of neck dysfunctions. OBJECTIVE: To evaluate pain, deep neck flexor (DNF) performance, disability, and head and neck posture of individuals with TMD with and without OC. METHODS: In this cross-sectional study, 57 individuals were divided into a group with TMD and OC (n= 31) and a group with TMD without OC (n= 26). Self-reported pain intensity, masticatory and neck muscles pressure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…Because of the high prevalence of OS in individuals with TMD, the primary study aimed to investigate if jaw and neck symptoms (e.g., pain, disability, muscle performance, and posture) were more intensified in individuals with TMD with OS compared with those without OS (Tavares et al, 2023). The findings of the primary study showed a decreased muscle performance and increased neck disability in individuals with TMD and OS compared with those without OS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the high prevalence of OS in individuals with TMD, the primary study aimed to investigate if jaw and neck symptoms (e.g., pain, disability, muscle performance, and posture) were more intensified in individuals with TMD with OS compared with those without OS (Tavares et al, 2023). The findings of the primary study showed a decreased muscle performance and increased neck disability in individuals with TMD and OS compared with those without OS.…”
Section: Methodsmentioning
confidence: 99%
“…This is a cross‐sectional study and secondary analysis of a study conducted from April to November 2019 and developed jointly between the departments of physical therapy, dentistry, and surgery at the Federal University of Rio Grande do Norte (Natal, Brazil). Because of the high prevalence of OS in individuals with TMD, the primary study aimed to investigate if jaw and neck symptoms (e.g., pain, disability, muscle performance, and posture) were more intensified in individuals with TMD with OS compared with those without OS (Tavares et al., 2023). The findings of the primary study showed a decreased muscle performance and increased neck disability in individuals with TMD and OS compared with those without OS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations